Uso de marcadores moleculares, como base en el mejoramiento genético del género Passiflora L. - Sánchez, Inés; Angel, Fernando; Fajardo, Diego; Castillo, María Fernanda; Lobo Arias, Mario; Tohme, Joseph M.; Roca, W. (1998)
One hundred twenty five accessions of Passiflora (granadillas, parchitas, curubas, badea and passion fruits) belonging to 26 species of the genus were characterized using 50 RAPD markers. Furthermore 35 accessions belonging to 12 species were analyzed by RFLPs of chloroplast DNA. RAPDs markers showed a high degree of genetic diversity within P. ligularis, P. maliformis and P. edulis. In the subgenus Tacsonia, similarity among accessions was high, indicating inter-species gene flow which is very important to traditional and molecular breeding studies of "curubas" (P. mollissima and P. sp. India). RFLPs analysis indicated high intra-specific polymorphism in P. ligularis and P. maliformis. DICE correlation from RAPD and RFLP data was r-0.745. Introgressions, gene flow, new hybrids, and elucidation of phylogeny can be initiated now using data presented here.